In silico analysis and prediction of transcription factors of the proteins interacting with astrocyte elevated gene-1. (June 2021) - Sriramulu, Sushmitha; Nandy, Suman K.; Ganesan, Harsha; Banerjee, Antara; Pathak, Surajit
Graphical abstract: Highlights: Gene Ontology analysis of AEG-1 and its interactors. Cross-talk between various AEG-1 interactors and its associated pathways. PTCH-1 & CREBBP are direct interactors of AEG-1, plays a role in Cancer Pathways. AEG-1 and its interactor proteins as biomarkers and therapeutic targets. Abstract: Multifunctional in nature, the protein Astrocyte Elevated Gene-1 (AEG-1) controls several cancers through protein-protein interactions. Although, specific physiological processes and molecular functions linked with AEG-1 interactors remain unclear. In our present study, we procured the data of AEG-1 interacting proteins and evaluated their biological functions, associated pathways, and interaction networks using bioinformatic tools. A total of 112 proteins experimentally detected to interact with AEG-1 were collected from various public databases. DAVID 6.8 Online tool was utilized to identify the molecular functions, biological processes, cellular components that aid in understanding the physiological function of AEG-1 and its interactors in several cell types. With the help of integrated network analysis of AEG-1 interactors using Cytoscape 3.8.0 software, cross-talk between various proteins, and associated pathways were revealed. Additionally, the Enrichr online tool was used for performing enrichment of transcription factors of AEG-1 interactors' which further revealed a closely associated self-regulated interaction network of a variety of transcription factors that shape the expression of AEG-1 interacting proteins. As a whole, the study calls for better understanding and elucidation of the pathways and biological roles of both AEG-1 and its interactor proteins that might enable their application as biomarkers and therapeutic targets in various diseases in the very near future.